Pengetahuan Ibu dengan Kesiapan Memilih Alat Kontrasepsi Pasca Persalinan pada Ibu Hamil Trimester III - Ni Kadek Sukreni; Cut Mutiya Bunsal; Petronela Mamentu (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2025)
Postpartum contraception is a contraceptive method given to coupery within les of child bearing age after deliv 42 days. The purpose of postpartum contraception is to space pregnancies, by ending fertility, avoiding unwanted pregnancies. The purpose of this study was to find mid the correlation between the level of maternal knowledge with the readiness to choose postpartum contraception in pregnant women in the third trimester at the 3rd grade hospital of Bhayangkara, Manado. The study was conducted using a correlation analytical method with a Cross Sectional design. The sample of respondents was 34 people. Using the Purposive Sampling technique. Data collection using a questionnaire. Analyzed with the Nonparametric Chi Square statistical test. The research results obtained show that the p-value= 0.001 is less than a = 0.05, Which means there is a correlation between knowledge with readiness to choose postpartum contraception in pregnant women in the third trimester.